Current Therapeutic Strategies for Adipose Tissue Defects/Repair Using Engineered Biomaterials and Biomolecule Formulations - Mahoney, Christopher M.; Imbarlina, Cayla; Yates, Cecelia C.; Marra, Kacey G. (Frontiers in Pharmacology, 2018)
Tissue engineered scaffolds for adipose restoration/repair has significantly evolved in recent years. Patients requiring soft tissue reconstruction, caused by defects or pathology, require biomaterials that will restore void volume with new functional tissue. The gold standard of autologous fat grafting (AFG) is not a reliable option. This review focuses on the latest therapeutic strategies for the treatment of adipose tissue defects using biomolecule formulations and delivery, and specifically engineered biomaterials. Additionally, the clinical need for reliable off-the-shelf therapies, animal models, and challenges facing current technologies are discussed.